2019
DOI: 10.1111/php.13089
|View full text |Cite
|
Sign up to set email alerts
|

NLOphoric Triphenylamine Derived Donor‐π‐Acceptor‐π‐Donor Based Colorants: Synthesis, Spectroscopic, Density Functional Theory and Z‐scan Studies

Abstract: Three Donor-p-Acceptor-p-Donor type styryl dyes (5a-c) with different secondary donors are synthesized and characterized to study their nonlinear and linear optical properties. The structure-property relationships of the dyes are described in the light of systematic photophysical and theoretical investigations. The photophysical characteristics of 5a-c are influenced by the polarity of the medium, with an appreciable bathochromic shift in emission (5b = 81 nm) and large Stoke shifts (5b = 104-173 nm) in polar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…More drastic effects for 5 c support the above hypothesis where planarization between julolidine and dicyano vinylene can smoothen CT. On comparing the synthesized fluorophores with the reported analogue 1 , it is observed that substituting different donors of varying donating strength at the opposite end of the fixed donor results in enhanced optical properties. Furthermore, when these fluorophores were compared with our previously reported fluorophores, having a similar structure but freely rotating/twisted triphenylamine as a fixed donor, the fluorophores from this work gave enhance optical properties . Thus, fluorophores with such a framework where one donor is fixed with a rigid group and varying D 2 with the different N‐substituents can lead to excellent push‐pull systems with enhance optical properties.…”
Section: Resultsmentioning
confidence: 56%
“…More drastic effects for 5 c support the above hypothesis where planarization between julolidine and dicyano vinylene can smoothen CT. On comparing the synthesized fluorophores with the reported analogue 1 , it is observed that substituting different donors of varying donating strength at the opposite end of the fixed donor results in enhanced optical properties. Furthermore, when these fluorophores were compared with our previously reported fluorophores, having a similar structure but freely rotating/twisted triphenylamine as a fixed donor, the fluorophores from this work gave enhance optical properties . Thus, fluorophores with such a framework where one donor is fixed with a rigid group and varying D 2 with the different N‐substituents can lead to excellent push‐pull systems with enhance optical properties.…”
Section: Resultsmentioning
confidence: 56%
“…2-(1-(4-(diphenylamino)phenyl)ethylidene)malononitrile ( 2) [16]. A mixture of 1 (1 mmol) and malononitrile (1 mmol) in a NH 4 AcO/AcOH buffer 10 ml were irradiated in a microwave at 120°C, 300 W for 4 min.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The synthesis of compounds 3a-d is presented in Scheme 1. At the first step 1-(4-(diphenylamino)phenyl)ethan-1-one ( 1) was converted to 2-(1-(4-(diphenylamino)phenyl) ethylidene)malononitrile ( 2) in the presence of NH 4 OAc/AcOH using microwave irradiation (MWI) by improved synthetic methods with higher yield [16]. Final products (3a-d) were…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[12] To reduce the energy difference between the HOMO and LUMO of the sensitizers and enhance the performance of DSSCs, researchers introduced quadrupolar structures such as D-π-A-π-D and D-π-A-π-A [13][14][15][16] and the octapolar (D-π-) 3 A or (A-π-) 3 D, [17] resulting in structures that display a large band adsorption spectra. [18] As the sensitizer is vital in DSSC devices, anchoring plays an important role as the unit that ensures the binding of the sensitizer to the semiconductor surface. After cyanovinyl carboxylic acid, phosphonic acid is the mainly used anchor group in the field of organic electronics.…”
mentioning
confidence: 99%